Contaminant diversity on Umiujaq territory, Nunavik, Canada ... : La diversité des contaminants sur le territoire d’Umiujaq, Nunavik, Canada ... - Thora Herrmann; Fabienne Joliet; Julien Gigault; Manon Gibaud; Véronique Coxam; Laine Chanteloup; Gaud Dervilly; Najat Bhiry; Danielle Cloutier; Anne-Julia Rollet; Beatriz M. Funatsu; Armelle Decaulne (LabEx DRIIHM, 2024)
The quality of the Umiujaq socio-ecosystem is assessed by examining the presence of contaminants in its territory. Various objects are of crucial interest: (i) the landfill, (ii) the river, (iii) sediments in the watersheds, (iv) fish in the river and at its mouth, (v) bivalves in the coastal zone, (vi) but also the whole of the indigenous territory. Several samples of different materials were collected at varying distances from the village, in 2022 and 2023. Despite Inuit being peoples of the sea, discussions with local residents highlighted their interest in the watercourses and the resources they support. Results show that traces of contaminants are similar to those found in other Inuit communities in the polar regions. Here, we present the preliminary, multidisciplinary results obtained over the past year, along with the most recent fieldwork. An emic approach was used to raise the question of the edibility of local foods in the vicinity of the landfill, and to study disturbances induced by climate ... : La qualité du socio-écosystème d'Umiujaq est examinée à travers la présence de contaminants sur son territoire. Différents objets sont d'un intérêt crucial : (i) la décharge, (ii) la rivière, (iii) les sédiments dans les bassins versants, (iv) les poissons de la rivière, de l’embouchure, (v) les bivalves dans la zone côtière, (vi) mais aussi le territoire autochtone de vie pratiqué dans son entièreté. Plusieurs échantillons de différents matériaux ont été prélevés à plus ou moins grande distance du village, en 2022 et 2023. Bien que les Inuit soient un peuple de la mer, les échanges avec les habitants soulignent leur intérêt pour les cours d’eau et la ressource qu’ils abritent. Les résultats montrent que les traces de contaminants sont similaires à celles d'autres communautés inuites dans les régions polaires. Nous présentons ici les résultats préliminaires et multidisciplinaires obtenus au cours de la dernière année, ainsi que les résultats des travaux de terrain les plus récents. Une approche émique a ...